APLIKASI BEBERAPA DOSIS ABU SERBUK GERGAJI DAN PUPUK HIJAU JENIS LEGUMINOCEAE TERFORMULASI SEBAGAI PEMACU PERTUMBUHAN SEMAI Eucalyptus pellita F. MUELL PADA MEDIUM GAMBUT - Adhiatma, Muhammad Jaya; Mardhiansyah, M.; Budiani, Evi Sri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Eucalyptus pellita is one of plants that was developved as industrial timber plantations (ITP) and has entered third rotations in Riau. Overlay peat medium is handicap ITP business in Riau. Therefore it is urgent to determine treatment for the improvement of the peat medium. This research aims to determine influence of ash saw dust and green fertilizer type leguminoceae formulated to Eucalyptus pellita seedlings in peat medium and the best dosage to growth of Eucalyptus pellita seedlings. Research using randomized complete design (RCD) consist of five treatments and four replications and five units trial. T0 = No provision of ash saw dust and green fertilizer type leguminoceae formulated ; T1 = 125 gr/polybag, T2 = 225 gr/polybag, T3 = 325 gr/polybag,and T4 = 425 gr/polybag. Research proved that the aplication in peat medium can increase the quality of Eucalyptus pellita seedlings. The aplication with a dosages 425 gr/polybag in peat medium is the best treatment to percent of live (100,00%), the height growth (23,44 cm) and top root/ratio (2,00). Keywords:Eucalyptus pellita F. Muell, ash saw dust and green fertilizer type leguminoceae formulated, peat medium